Method for improving water resistance of alkaline earth aluminate long-afterglow luminescent material

By coating silica on the surface of the alkaline earth aluminate long afterglow luminescent material and forming a calcium silicate layer, the problem of easy decomposition of the material when exposed to water is solved, and the effect of significantly improving water resistance and temperature resistance is achieved.

CN119552649APending Publication Date: 2025-03-04MINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411772139.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Alkaline aluminate long afterglow luminescent materials are prone to decomposition when exposed to water and have poor temperature resistance, which limits their application range.

Method used

The surface of the alkaline earth aluminate long afterglow luminescent material is coated with silica and carried out a coating reaction under ultrasonic conditions, and then a calcium silicate layer is formed to improve the water resistance and temperature resistance of the material.

Benefits of technology

It significantly improves the water resistance and temperature resistance of alkaline earth aluminate long afterglow luminescent materials, extends its service life and improves the reliability of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552649A_ABST
    Figure CN119552649A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving water resistance of an alkaline earth aluminate long-afterglow luminescent material, and belongs to the field of long-afterglow self-luminescent materials. The invention aims to solve the problems that the existing alkaline earth aluminate long-afterglow luminescent material is easy to decompose when encountering water and poor in temperature resistance. The method comprises the following steps: 1, dispersing alkaline earth aluminate long afterglow luminescent powder into a mixed solution of ethanol and water; 2, adjusting the pH value; 3, adding tetraethyl silicate for coating reaction; 4, dissolving calcium chloride, ammonium chloride and urea in deionized water to obtain a mixed solution; and 5, adding the silicon dioxide coated alkaline earth aluminate long-afterglow luminescent material into the mixed solution, and heating at high temperature. The method is used for improving the water resistance of the alkaline earth aluminate long-afterglow luminescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of long afterglow self-luminous materials. Background Art

[0002] Long afterglow self-luminous materials can store the absorbed energy without consuming power, and emit visible light of various colors in a dark environment. They are widely used in living lighting, craft decoration, disaster prevention, fire fighting, military and other fields. Among them, the alkaline earth aluminate series of luminescent materials are the best light-storage luminescent materials with long afterglow luminescence performance known so far. Compared with traditional long afterglow luminescent materials, they have more beneficial properties, such as higher luminous efficiency, longer afterglow time and stable chemical properties. However, the alkaline earth aluminate long afterglow luminescent material is a weakly acidic salt. The fine powder obtained after synthetic grinding has a high specific surface area and is easily decomposed in water. Moreover, the luminescent material is synthesized in a weak reducing atmosphere, and will lose its light storage performance when treated at high temperature in an oxidizing atmosphere (such as air). Therefore, how to solve the problem of easy decomposition of alkaline earth aluminate long afterglow luminescent materials in water and poor temperature resistance is still the main bottleneck of current applications. Summary of the invention

[0003] The present invention aims to solve the problems that the existing alkaline earth aluminate long afterglow luminescent material is easily decomposed when in contact with water and has poor temperature resistance, and further provides a method for improving the water resistance of the alkaline earth aluminate long afterglow luminescent material.

[0004] A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material is carried out according to the following steps:

[0005] 1. Dispersing alkaline earth aluminate long afterglow luminescent powder into a mixed solution of ethanol and water to obtain a luminescent powder dispersion;

[0006] 2. Adding ammonia water dropwise into the luminescent powder dispersion until the pH value is 9 to 12, thereby obtaining a luminescent powder dispersion after pH adjustment;

[0007] 3. Adding tetraethyl silicate to the luminescent powder dispersion after pH adjustment, and then coating reaction under ultrasonic conditions, and finally centrifugation drying to obtain a silica-coated alkaline earth aluminate long afterglow luminescent material;

[0008] 4. dissolving calcium chloride, ammonium chloride and urea in deionized water to obtain a mixed solution;

[0009] 5. Adding the alkaline earth aluminate long afterglow luminescent material coated with silica into the mixed solution and mixing it by ultrasonic, then heating it at high temperature, and finally centrifugally drying it to obtain the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate.

[0010] The beneficial effects of the present invention are:

[0011] The present invention uses silicon dioxide coated on the surface of the alkaline earth aluminate long afterglow luminescent material as a raw material, which is subsequently etched along with the formation of calcium silicate, thereby achieving in-situ coating of the calcium silicate layer and improving the water resistance and temperature resistance of the luminescent powder.

[0012] The preparation operation of the invention is simple and the material cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The scanning electron microscope images of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a and b are uncoated alkaline earth aluminate long afterglow luminescent powder, c and d are alkaline earth aluminate long afterglow luminescent materials coated with calcium silicate;

[0014] Figure 2 The transmission electron microscope images of the calcium silicate-coated alkaline earth aluminate long afterglow luminescent material prepared in Example 1, a is a TEM image, b is a HAADF-STEM image, c is an overlap image of Al and Ca, d is a Si element distribution image, e is a Sr element distribution image, f is an O element distribution image, g is a Dy element distribution image, and h is a Eu element distribution image;

[0015] Figure 3 : is the fluorescence emission spectrum of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a is the uncoated alkaline earth aluminate long afterglow luminescent powder, b is the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate;

[0016] Figure 4 The water resistance diagram of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a is the uncoated alkaline earth aluminate long afterglow luminescent powder, b is the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate;

[0017] Figure 5 This is a graph showing the temperature resistance of the calcium silicate-coated alkaline earth aluminate long afterglow luminescent material prepared in Example 1. DETAILED DESCRIPTION

[0018] Specific implementation method 1: This implementation method is a method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material, which is carried out according to the following steps:

[0019] 1. Dispersing alkaline earth aluminate long afterglow luminescent powder into a mixed solution of ethanol and water to obtain a luminescent powder dispersion;

[0020] 2. Adding ammonia water dropwise into the luminescent powder dispersion until the pH value is 9 to 12, thereby obtaining a luminescent powder dispersion after pH adjustment;

[0021] 3. Adding tetraethyl silicate to the luminescent powder dispersion after pH adjustment, and then coating reaction under ultrasonic conditions, and finally centrifugation drying to obtain a silica-coated alkaline earth aluminate long afterglow luminescent material;

[0022] 4. dissolving calcium chloride, ammonium chloride and urea in deionized water to obtain a mixed solution;

[0023] 5. Adding the alkaline earth aluminate long afterglow luminescent material coated with silica into the mixed solution and mixing it by ultrasonic, then heating it at high temperature, and finally centrifugally drying it to obtain the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate.

[0024] The beneficial effects of this embodiment are:

[0025] In this embodiment, silicon dioxide coated on the surface of the alkaline earth aluminate long afterglow luminescent material is used as a raw material, which is subsequently etched along with the formation of calcium silicate, thereby achieving in-situ coating of the calcium silicate layer and improving the water resistance and temperature resistance of the luminescent powder.

[0026] The preparation operation of this embodiment is simple and the material cost is low.

[0027] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the concentration of the alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion described in step 1 is 0.1 g / mL to 0.5 g / mL; the volume ratio of ethanol to water in the mixed solution of ethanol and water described in step 1 is 1:(0.05 to 0.2). Others are the same as specific embodiment 1.

[0028] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step 2, under the condition of a dropwise addition speed of 1d / s to 2d / s, ammonia water is added dropwise to the luminescent powder dispersion until the pH value is 9 to 12; the mass percentage of ammonia water in step 2 is 25% to 28%. Other aspects are the same as specific implementation method 1 or 2.

[0029] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the mass of tetraethyl silicate in step 3 is 0.1% to 0.3% of the mass of alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion after pH adjustment. The rest is the same as specific embodiments 1 to 3.

[0030] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 3, the coating reaction is carried out for 0.5 h to 2 h under the conditions of ultrasonic power of 70 W to 100 W and temperature of 55° C. to 65° C. The rest is the same as specific embodiments 1 to 4.

[0031] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the concentration of calcium chloride in the mixed solution described in step 4 is 0.015 g / mL to 0.03 g / mL, the concentration of ammonium chloride is 0.015 g / mL to 0.03 g / mL, and the concentration of urea is 0.12 g / mL to 0.15 g / mL. Others are the same as specific embodiments 1 to 5.

[0032] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the ultrasonic mixing in step 5 is carried out under the condition of an ultrasonic power of 100W to 150W for 10 to 30 minutes. The rest is the same as specific embodiments 1 to 6.

[0033] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the high temperature heating in step 5 is specifically heating at a temperature of 100° C. to 180° C. for 6 h to 18 h. The rest is the same as specific embodiments 1 to 7.

[0034] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the mass of calcium chloride in the mixed solution described in step 5 is 2 to 8 times that of the alkaline earth aluminate long afterglow luminescent material coated with silicon dioxide. The rest is the same as specific embodiments 1 to 8.

[0035] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the centrifugal drying described in step 3 and step 5 is specifically carried out according to the following steps: centrifugation for 2 min to 5 min at a rotation speed of 2000 rpm to 3500 rpm, and then drying for 5 h to 12 h at a temperature of 40° C. to 60° C. The rest is the same as specific embodiments 1 to 9.

[0036] The following examples are used to verify the beneficial effects of the present invention:

[0037] Embodiment 1:

[0038] A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material is carried out according to the following steps:

[0039] 1. dispersing alkaline earth aluminate long afterglow luminescent powder in a mixed solution of ethanol and water to obtain a luminescent powder dispersion;

[0040] The concentration of the alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion is 0.1 g / mL; the volume ratio of ethanol to water in the mixed solution of ethanol and water is 1:0.1;

[0041] 2. Under the condition of a dropwise addition speed of 1 d / s, ammonia water is added dropwise to the luminescent powder dispersion until the pH value is 11, thereby obtaining a luminescent powder dispersion after pH adjustment;

[0042] The mass percentage of the ammonia water is 25%;

[0043] 3. Add tetraethyl silicate to the luminescent powder dispersion after pH adjustment, then carry out coating reaction for 1 hour under the conditions of ultrasonic power of 80W and temperature of 60°C, and finally centrifuge and dry to obtain a silica-coated alkaline earth aluminate long afterglow luminescent material;

[0044] The mass of the tetraethyl silicate is 0.2% of the mass of the alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion after pH adjustment;

[0045] 4. dissolving calcium chloride, ammonium chloride and urea in deionized water to obtain a mixed solution;

[0046] The concentration of calcium chloride in the mixed solution is 0.015 g / mL, the concentration of ammonium chloride is 0.015 g / mL, and the concentration of urea is 0.12 g / mL;

[0047] 5. Add the silica-coated alkaline earth aluminate long afterglow luminescent material to the mixed solution, mix for 15 minutes under the condition of ultrasonic power of 100 W, then place in a Teflon-lined stainless steel autoclave, heat for 12 hours at a temperature of 160° C., and finally centrifuge and dry to obtain the calcium silicate-coated alkaline earth aluminate long afterglow luminescent material;

[0048] The mass of calcium chloride in the mixed solution is 6 times that of the alkaline earth aluminate long afterglow luminescent material coated with silicon dioxide.

[0049] The alkaline earth aluminate long afterglow luminescent powder described in step 1 is SrAl2O4:Eu 2+ ,Dy 3+ Luminescent powder (Dalian Luming Luminescent Technology Co., Ltd., PLO-7C).

[0050] The centrifugal drying in step 3 and step 5 is specifically carried out according to the following steps: centrifugation for 5 minutes at a rotation speed of 2000 pm, and then drying for 12 hours at a temperature of 60°C.

[0051] Figure 1The scanning electron microscope images of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a and b are uncoated alkaline earth aluminate long afterglow luminescent powder, c and d are alkaline earth aluminate long afterglow luminescent materials coated with calcium silicate. It can be seen from the figure that before coating, the alkaline earth aluminate luminescent powder presents a smooth polyhedral morphology, and after coating, the surface of the alkaline earth aluminate luminescent powder becomes rough, which may be the calcium silicate grown on the surface.

[0052] Figure 2 The transmission electron microscope images of the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate prepared in Example 1, a is a TEM image, b is a HAADF-STEM image, c is an overlap image of Al and Ca, d is a Si element distribution image, e is a Sr element distribution image, f is an O element distribution image, g is a Dy element distribution image, and h is a Eu element distribution image. It can be seen from the figure that a thick layer of material grows on the surface of the alkaline earth aluminate. The element distribution more directly shows that the Ca and Si elements are mainly distributed in the outer shell, while the internal structure is mainly composed of Sr, Al, Eu and Dy elements, and the Ca and Si elements are evenly distributed, indicating that the coating is dense and uniform.

[0053] Figure 3 The fluorescence emission spectra of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a is the uncoated alkaline earth aluminate long afterglow luminescent powder, and b is the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate. The peak type and peak position of the emission spectrum of the sample before and after coating are almost unchanged, and there is an emission peak at 515nm, indicating that the crystal structure of the luminescent pigment has not changed after coating. However, the emission peak intensity is reduced after coating. It is calculated that the fluorescence intensity of the sample after coating is 91% of that before coating, indicating that the calcium silicate coating layer has little effect on the luminescence performance.

[0054] When the alkaline earth aluminate long afterglow luminescent powder comes into contact with water, it will slowly undergo hydrolysis reaction to generate aluminum hydroxide, which will increase the pH of the system. Therefore, the degree of hydrolysis of the luminescent powder can be determined by testing the pH value in the system, thereby judging its water resistance. The specific test method is as follows: the water resistance of the sample is measured using a PHS-2F digital acidity meter. During the test, 1.0g of the powder sample is added to 20g of deionized water, and the change in the pH of the solution is tested at room temperature. Figure 4 The water resistance diagram of the alkaline earth aluminate long afterglow luminescent powder before and after calcium silicate coating in Example 1, a is the uncoated alkaline earth aluminate long afterglow luminescent powder, and b is the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate. As can be seen from the figure, when it is not coated (the coating amount is zero), the sample shows extremely poor water resistance. After coating with calcium silicate, the change in pH value is small, and the water resistance of the sample is improved.

[0055] When testing the thermal stability, the luminescent powder is heated in air at a temperature ranging from room temperature to 300°C for 30 minutes. After the heat treatment, the fluorescence intensity of the luminescent powder is retested. Figure 5 This is a graph showing the temperature resistance of the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate prepared in Example 1. As can be seen from the graph, the thermal stability is significantly improved after calcium silicate coating. After heat treatment at 300°C for 30 minutes, the emission peak intensity can still be maintained at more than 75%, indicating that the calcium silicate coating layer can effectively block the effect of high temperature on the luminescent powder.

Claims

1. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent materials, characterized in that It is carried out in the following steps:

1. Dispersing alkaline earth aluminate long afterglow luminescent powder into a mixed solution of ethanol and water to obtain a luminescent powder dispersion; 2. Adding ammonia water dropwise into the luminescent powder dispersion until the pH value is 9 to 12, thereby obtaining a luminescent powder dispersion after pH adjustment; 3. Adding tetraethyl silicate to the luminescent powder dispersion after pH adjustment, and then coating reaction under ultrasonic conditions, and finally centrifugation drying to obtain a silica-coated alkaline earth aluminate long afterglow luminescent material; 4. dissolving calcium chloride, ammonium chloride and urea in deionized water to obtain a mixed solution; 5. Adding the alkaline earth aluminate long afterglow luminescent material coated with silica into the mixed solution and mixing it by ultrasonic, then heating it at high temperature, and finally centrifugally drying it to obtain the alkaline earth aluminate long afterglow luminescent material coated with calcium silicate.

2. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent materials according to claim 1, characterized in that The concentration of the alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion described in step one is 0.1 g / mL to 0.5 g / mL; the volume ratio of ethanol to water in the mixed solution of ethanol and water described in step one is 1:(0.05 to 0.2).

3. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material according to claim 1, characterized in that In step 2, under the condition of a dropwise addition speed of 1 d / s to 2 d / s, ammonia water is added dropwise to the luminescent powder dispersion until the pH value is 9 to 12; the mass percentage of ammonia water in step 2 is 25% to 28%.

4. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent materials according to claim 1, characterized in that The mass of the tetraethyl silicate described in step 3 is 0.1% to 0.3% of the mass of the alkaline earth aluminate long afterglow luminescent powder in the luminescent powder dispersion after pH adjustment.

5. The method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material according to claim 1, characterized in that In step 3, the coating reaction is carried out for 0.5 h to 2 h under the conditions of ultrasonic power of 70 W to 100 W and temperature of 55° C. to 65° C.

6. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent materials according to claim 1, characterized in that The concentration of calcium chloride in the mixed solution described in step 4 is 0.015 g / mL to 0.03 g / mL, the concentration of ammonium chloride is 0.015 g / mL to 0.03 g / mL, and the concentration of urea is 0.12 g / mL to 0.15 g / mL.

7. A method for improving the water resistance of alkaline earth aluminate long afterglow luminescent materials according to claim 1, characterized in that The ultrasonic mixing described in step 5 is specifically mixing for 10 minutes to 30 minutes under the condition of ultrasonic power of 100W to 150W.

8. The method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material according to claim 1, characterized in that The high temperature heating described in step 5 is specifically heating at a temperature of 100° C. to 180° C. for 6 h to 18 h.

9. The method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material according to claim 1, characterized in that The mass of calcium chloride in the mixed solution described in step 5 is 2 to 8 times that of the alkaline earth aluminate long afterglow luminescent material coated with silicon dioxide.

10. The method for improving the water resistance of alkaline earth aluminate long afterglow luminescent material according to claim 1, characterized in that The centrifugal drying described in step 3 and step 5 is specifically carried out according to the following steps: centrifugation for 2 min to 5 min at a rotation speed of 2000 rpm to 3500 rpm, and then drying for 5 h to 12 h at a temperature of 40° C. to 60° C.